Towards a Poetry of Silence: Stéphane Mallarmé and Juan Ramón Jiménez - Mervyn Coke-Enguídanos (Studies in 20th & 21st Century Literature, 1983)
In an era of apparent dissolution, "la Obra" of Juan Ramón Jiménez, like "l'Oeuvre" of Stéphane Mallarmé, has for its goal the attainment of timelessness. In both poets, the concept of absolute Time—the timelessness of eternal Time—is yoked with the ideal of silence. But this is no ordinary silence, and certainly not the kind that results from inadequacy of expression. It is the silence of perfection, the expression of the ineffable: pure Poetry. Since the poetic language is the silent language of thought, both Mallarmé and Juan Ramón seek to convey the pure idea. In so doing, both must stringently eliminate whatever is not essential in their poetry. The astonishing paradox, central to Mallarmé and Juan Ramón alike, is the urge to create an "unwritten" poetry.
Keywords: Stéphane Mallarmé; Juan Ramón Jiménez; French poetry; Spanish poetry; la obra; l& #x27; Oeuvre; timelessness; absolute time; time; eternal time; eternal; silence; expression; perfection; poetry